The cointegration analysis of the Lithuania’s macroeconomic indicators - Firkovič, Viktorija (Lietuvos matematikos rinkinys, 2002)
Most of the existing technigues of the macroeconomic indicators analysis can not be succefully applied to the common situation of a limited data set. The goal of the work is to estimate the evolution of Lithuania’s macroeconomic indicators using the vector cointegrated anlysis combined with the recursive metod proposed by R. Rudzkis and G. Vilutis (2001).